THE INFLUENCE OF DPK, NPF, AND BOPO ON ROA ISLAMIC COMMERCIAL BANKS IN INDONESIA - Nasution, Lailan Azmi; Siregar, Pani Akhiruddin; Sari, Yulia; Patimah, Patimah; Pasaribu, Novita Sari (Proceeding International Seminar of Islamic Studies, 2024)
This study was conducted to formulate whether DPK, NPF, and BOPO affect the ROA of Islamic Commercial Banks in Indonesia. The type of research data with secondary data sourced from the Financial Performance of Islamic Commercial Banks through the publication of Sharia banking Statistics, Financial Services Authority (SPS-OJK). SPS-OJK is a publication media that presents data on Sharia banking in Indonesia. The research sample was taken periodically in the form of monthly data from January 2020 to September 2023. At least, the amount of data that can be further analyzed is 45 data. Sample withdrawal technique with simple random sampling. The research results are as follows: (1) The estimation model shows an R2 value of 0.551 which represents the coefficient of determination. This means that 55.10% of the variation in the dependent variable can be explained by the independent variables in this model. The remaining 44.90% is explained by other causes that are not included in the model; (2) The regression model on the independent variables simultaneously affects the dependent variable so that the independent variable regression model can be used to predict the dependent variable; and (3) This study produces the output of not only DPK but also BOPO which has a significant effect on the ROA of Islamic Commercial Banks in Indonesia. Except that, NPF has no effect and is not significant on the ROA of Islamic Commercial Banks in Indonesia.